Consistency of Response to Sumatriptan/Naproxen Sodium in a Randomized Placebo‐Controlled, Cross‐Over Study for the Acute Treatment of Migraine in Adolescence. Issue 4 (April 2015) - Winner, Paul; Linder, Steven; Hershey, Andrew D.
<x xml:space="preserve">Abstract</x> A multi‐centered, randomized, placebo‐controlled, early intervention, cross‐over study was conducted to evaluate the consistency of response of sumatriptan/naproxen sodium 85/500 mg (S/NS) over 4 attacks in the acute treatment of migraine in adolescents. Inclusion of subjects was dependent on their age of 12‐17 years, frequency, and history of migraine headaches (1‐8 per month) over the previous 6 months prior to screening and generally healthy males and females of non‐childbearing potential that were not on excluded medications. Subjects were instructed to treat within 1 hour of pain onset, including when the pain was still mild. Subjects were randomized in a double‐blind fashion using a computer‐generated randomization list in which the study drug was prepared prior to study start, and subjects were allocated to a number in sequential order for each site. Each site was allocated number blocks in sets of 10 depending of the rate of enrollment. The objective of this study was to examine the efficacy of S/NS vs placebo in the primary end‐points of pain‐free response at 2 hours (2hPF), 24‐hour sustained pain‐free response (24hPF), and pain‐free response at 2 hours with early intervention (2hPFE) calculated as percentage out of all attacks. In the study, 94 subjects treated 347 attacks in total: treating 277 with S/NS and 70 with placebo. Compared with placebo, S/NS produced higher 2hPF rates (S/NS 37%, placebo 18%; P < .004), and 2hPFE with rates (S/NS 32%, 18% placebo; P < .03). Compared with placebo, 24hPF rates were S/NS 86%, placebo 78%, P < .17, which were higher than placebo but not clinically significant. 2hPF was reported in at least 2 of the 3 migraines treated with S/NS in 40.4% of subjects. 24hPF was reported in at least 2 of the 3 migraine treated with S/NS in 86.2% subjects. Adverse reactions were generally low and comparable between S/NS and placebo.